Analisis Biaya Promosi Terhadap Peningkatan Penjualan Tiket Pada PT Garuda Indonesia (Persero) TBK Banch Office Lampung - SONIA SAPITRI; Damayanti Damayanti (Jurnal Kompetitif Bisnis, 2022)
The study aims to determine promotion activities, promotion costs, sales revenue and analyze the significance level of the effect of promotion costs on increasing ticket sales revenue at PT Garuda Indonesia (Persero) TBK Branch Office Lampung. The sampling in this study is 48 samples using monthly reports of promotion costs and sales revenue for 4 years, starting from 2018-2021. The analytical method used is simple linear regression, t hypothesis test and coefficient of determination analysis using SPSS 25.0 software. The results showed that the independent variable of promotion costs had a significant effect on the dependent variable of sales revenue.